2015
DOI: 10.3748/wjg.v21.i20.6215
|View full text |Cite
|
Sign up to set email alerts
|

CD97 promotes gastric cancer cell proliferation and invasion through exosome-mediated MAPK signaling pathway

Abstract: CD97 promotes gastric cancer cell proliferation and invasion in vitro through exosome-mediated MAPK signaling pathway, and exosomal miRNAs are probably involved in activation of the CD97-associated pathway.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
81
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 99 publications
(85 citation statements)
references
References 39 publications
2
81
0
Order By: Relevance
“…MSC derived exosomes have been shown to promote vascularization via the P38 mitogen activated protein kinase (MAPK) pathway [45]. Additionally, published studies have shown that this pathway is triggered during exosome mediated cell proliferation albeit in cancer cells [46]. We therefore evaluated if the pulp cell derived exosomes triggered the MAPK pathway in DPSCs upon endocytosis.…”
Section: Resultsmentioning
confidence: 99%
“…MSC derived exosomes have been shown to promote vascularization via the P38 mitogen activated protein kinase (MAPK) pathway [45]. Additionally, published studies have shown that this pathway is triggered during exosome mediated cell proliferation albeit in cancer cells [46]. We therefore evaluated if the pulp cell derived exosomes triggered the MAPK pathway in DPSCs upon endocytosis.…”
Section: Resultsmentioning
confidence: 99%
“…Identification of the endocytic mechanism can provide valuable information to target EVs for therapeutic delivery. With respect to EV endocytosis, the clathrin pathway, caveolar pathway, phagocytosis, and even macropinocytosis have all been implicated in endocytosis of EVs (Mulcahy et al, 2014;Li et al, 2015;Alcayaga-Miranda et al, 2016). We observed energy dependence, dose dependence as well as dependence on membrane cholesterol indicating the involvement of the lipid raft/caveolar endocytic pathway.…”
Section: Discussionmentioning
confidence: 62%
“…CD97 has been shown to heterodimerize with the lysophosphatidic acid (LPA) receptor to amplify LPA‐initiated RHO‐dependent signalling and invasion in prostate cancer cells . CD97 has been shown to promote gastric cancer cell proliferation and invasion in vitro through exosome‐mediated MAPK signalling pathway . Furthermore, CD97 promoted tumour aggressiveness through the traditional G protein–coupled receptor‐mediated signalling in hepatocellular carcinoma …”
Section: Discussionmentioning
confidence: 99%